Analisis Sistem Pendukung Keputusan Seleksi Calon Anggota Organisasi IMM Menggunakan Metode SAW - Jaka Dernata Jaka; Rusydi Umar; Anton Yudhana (JATISI (Jurnal Teknik Informatika dan Sistem Informasi), 2022)
Acceptance of prospective new members is an activity that must be carried out in an organization to get good quality prospective members from the acceptance of members in the Muhammadiyah Student Association. The more prospective members who want to enter an organization, the more difficult it is to make decisions in selecting new prospective members. There are several organizations, the recruitment of prospective members is still mostly done professionally. This problem is caused by the absence of a system to be selected in the selection of new members. The Simple Additive Weighting (SAW) method was chosen to conduct this research because this method can create a weight value after each one, then rank the attributes on each alternative from all alternatives, the alternative is a prospective new member based on the criteria that have been determined by the committee. This research will produce a system to simplify and speed up the selection of new members and the selection committee in making decisions for new members of the Muhammadiyah Student Association.